The scaffolding of our thoughts : essays on Assyriology and the history of science in honor of Francesca Rochberg - Crisostomo, C. Jay; Escobar, Eduardo A.; Tanaka, Terri; Veldhuis, Niek; Rochberg, Francesca, 1952- (Ancient magic and divination, 2018)
Francesca Rochberg has for more than thirty-five years been a leading figure in the study of ancient science. Her foundational insights on the concepts of "science," "canon," "celestial divination," "knowledge," "gods," and "nature" in cuneiform cultures have demanded continual contemplation on the tenets and assumptions that underlie the fields of Assyriology and the History of Science. "The Scaffolding of Our Thoughts" honors this luminary with twenty essays, each reflecting on aspects of her work. Following an initial appraisal of ancient "science" by Sir Geoffrey Lloyd, the contributions in the first half explore practices of knowledge in Assyriological sources. The second half of the volume focuses specifically on astronomical and astrological spheres of knowledge in the Ancient Mediterranean.